PENGARUH KEPEMIMPINAN ETIS DAN EFIKASI DIRI TERHADAP KREATIVITAS KARYAWAN DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR SEBAGAI VARIABEL MEDIASI (Studi pada karyawan PLN UPT PERSERO Duri Kosambi) - Rianasta, Dzaki Raikhan; Yuniawan, Ahyar (Diponegoro Journal of Management, 2023)
ABSTRACT This study aims to analyze the effect of ethical leadership and self-efficacy on employee creativity through organizational member behavior as a mediating variable. The object of this research is PLN UPT PERSERO Duri Kosambi in West Jakarta. The population used in this study is PLN UPT PERSERO Duri Kosambi employees. The number of samples used was 82 respondents using a stratified proportional random sampling technique where the samples were obtained from various employees with different positions. The analytical tool used to test the hypothesis is Multiple Linear Regression with SPSS 20 software. The results of the study show that ethical leadership and self-efficacy through OCB have a positive and significant effect on employee creativity. Self-efficacy has a negative and insignificant effect on employee creativity. Then ethical leadership through OCB has a positive and not significant effect on employee creativity at PLN UPT PERSERO Duri Kosambi employees.